Role of Vitamin C on the viabilitys of the keratinocyte and HeLa cell with irradiation of UVB ray. - Iryani Andamari, Iryani Andamari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background:Ultraviolet B (UVB) exposure is one of the external factors which can cause reduction of cell viabillity through photochemistry reaction and can be managed using antioxydant. Failures of DNA repair and apoptosis have some important roles in photocarcinogenesis.Objective: This research is aimed to know the effect of vitamin C on the viability of UVB irradiated keratinocytes and HeLa cells.Method: This research employed a simple experimental method. Two groups of cells used in this research were: Group I normal foreskin keratinocytes passage III, and Group II HeLa cells. Each group was divided into 25 sub-groups consisting of 2x104 cells each, treated with vitamin C at 0, 6, 12, 40, 200 ÃÂµg/ml concentrations, and UVB irradiated (Phillips UVB TL4OW/12RS) at 0, 200, 400, 800, 1600 mJ/cm2 intensities. Each treatment was done in quintet. Viable cells were determined based on formazan blue reaction using ELISA-reader 550 nm 24 hours after treatment. The results were analyzed by independent t-test, one-way ANOVA, and multivariate analysis using three-way analysis of variance,Result: Vitamin C at 6, 12, 40, and 200 ug/m1 concentrations significantly increased normal keratinocyte and HeLa cells viability which were not irradiated by UVB, statistically significant, compared to normal keratinocyte and HeLa cells which were not treated with vitamin C. HeLa cells, which were irradiated by UVB at 200, 400, and 800, 1600 mJ/cm2 intensities and treated with vitamin C at 6, 12, 40 and 200 ug/ ml concentrations, statistically significant in decreasing cell viability.Conclusion: Vitamin C at 200 ÃÂµg/ml concentration, which was given to normal keratinocytes irradiated by UVB at 200, 400, 800, and 1600 mj/cm2 intensities used in this research showed its protection effect, thus enhancing the viability of the cell. Vitamin C 6, 12, 40 ug/ml, which were irradiated with UVB at 200, 400, 800, and 1600 mJ/cm2 intensities, did not show protection effect. HeLa cells were less resistant than normal keratinocytes to UVB irradiation at 200, 400, 800, and 1600 mj/cm2 intensities.Key words: vitamin-C, HeLa cell, keratinocyte, cell viability, UVB